DETAILED MORPHOLOGY OF THE RICH CONCENTRATED GALAXY CLUSTERS - Panko, E.; Sirginava, A.; Stepaniuk, A. (Одеські астрономічні публікації, 2018)
The results of the detailed analysis of the 2D distribution of galaxies in 28 rich galaxy clusters with signiﬁcant concentration to the cluster center are present. The analysis was executed in these directions: the detection of regular substructures and peculiarities in the galaxy distribution. The role of brightest cluster members was taken into account too. The input data were selected from “The Catalogue of Galaxy Clusters and Groups” and list of galaxies of Muenster Red Sky Survey. Concentrated galaxy clusters are evolved, virialized structures. Substructures in this type of clusters must be feeblemarked. Nevertheless we detected igniﬁcant part of concentrated galaxy clusters having diﬀerent kinds of peculiarities, namely crossing and divaricating ﬁlaments or X and Y-type peculiarities, as well as curved strips and short dense chains. 2 clusters having extremely density of galaxies were attributed as superconcentrated/compact type.